2019
DOI: 10.5195/emaj.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Business Process Reengineering and the Performance of Insurance Firms in Nigeria

Abstract: This study investigated the effect of business process reengineering on the performance of insurance firms in Nigeria, by employing two components of business process reengineering. Survey research design was adopted, through the administration of structured questionnaires on some selected staff of insurance companies at their head offices in Lagos, Nigeria. The research instrument was validated through content validity index (CVI), while the reliability of the research instrument was tested through test-retes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The population consists of the top and middle management staff in the selected Insurance Companies. The justifications for selecting twenty (20) Insurance Companies are owing to the fact that they are listed on Nigeria Stock Exchange and they are economically viable with strong equity assets base. The authors used total enumeration for the study sample size because the total population is not large.…”
Section: Methodology:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The population consists of the top and middle management staff in the selected Insurance Companies. The justifications for selecting twenty (20) Insurance Companies are owing to the fact that they are listed on Nigeria Stock Exchange and they are economically viable with strong equity assets base. The authors used total enumeration for the study sample size because the total population is not large.…”
Section: Methodology:-mentioning
confidence: 99%
“…in order to make up for the identified limitations of the study, the researchers suggested the following: Future research could take this investigation into only twenty (20) Insurance firms in Lagos State, further to determine effect of skills shiftonOrganisational Sustainability of Insurance Companies in other states such as, South-East, South-West, and Northern part of Nigeria where Insurance Companies were located. This paper explored the effect of skills shift, on Organisational Sustainability of selected Insurance Companies (in financial service sector), the findings of the study might have influenced the generalisability of the research findings in other industries.…”
Section: Conclusion / Recommendation: -mentioning
confidence: 99%